Implementation Of Akhlacul Karimah Values Through Al-qur'an Reading Activities At Nanda Al-manaf Primary School Sunggal District - Hernawan Syahputra Lubis; Ahmad Rizki (Yayasan Multidimensi Kreatif, 2024)
This research aims to find out how the Akhlakul Karimah Values ​​are implemented through Al-Qur'an Reading Activities at Nanda Al-Manaf Elementary School, Sunggal District. This research aims to determine the objective condition of students' morals through Al-Qur'an reading activities at Nanda Al-Manaf Elementary School, Sunggal District, to find out the form of akhlakul karimah applied at Nanda Al-Manaf Elementary School, Sunggal District, and to find out the supporting factors and obstacles in implementing akhlakul karimah values ​​at Nanda Al-Manaf Elementary School, Sunggal District. The type of research carried out was qualitative descriptive research. Data was collected through observation, interviews, documentation. The data obtained was then analyzed descriptively. The results of this research show that the objective condition of students' morals through Al-Qur'an reading activities at Nanda Al-Manaf Elementary School, Sunggal District is that they are implemented in akhlakul karimah values, namely religious values, honesty, discipline, independence, fond of reading, caring for the environment, respect, responsibility and love for the Koran. The forms of akhlakul karimah implemented at SD Nanda Al-Manaf, Sunggal District, are reading short verses, reading prayers before and after lessons, tadarruz, and throwing rubbish in its place. Meanwhile, the supporting and inhibiting factors are supporting factors, namely the example of school principals and teachers, the availability of facilities and infrastructure, the existence of cooperation between teachers and students. The inhibiting factor is that not all schools can set an example, and administration still needs to be improved.